A influência das Golden Shares no desempenho da empresa - Mainardi, Rodrigo Almeida (2022)
The relationship between the ownership structure and the performance of companies has been a subject of interest among academics, mainly to understand the efficiency of the golden share that makes government ownership a control mechanism. This study aims to analyze the influence of golden shares on the accounting performance of public traded companies that underwent privatization at a global level. To achieve this objective, the dynamic difference-in-differences (DID) method was used with Kernel Propensity Score Match (PSM) and a multilevel analysis. As a result, privatized companies that have golden shares are experienced more positive impact on market performance than companies privatized without it.